2005
DOI: 10.1097/01.shk.0000150549.45338.6c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dopamine and Norepinephrine on Systemic and Hepatosplanchnic Hemodynamics, Oxygen Exchange, and Energy Balance in Vasoplegic Septic Patients

Abstract: Dopamine is widely used to improve systemic and hepatosplanchnic hemodynamics and oxygenation during sepsis. However, some studies have suggest that norepinephrine may have beneficial effects on regional blood flow and metabolism, whereas dopamine might have deleterious effects related to redistribution of blood flow away from the intestinal mucosa or by decreasing directly the cell redox state. In 12 vasoplegic septic patients, we compared the effects of norepinephrine and dopamine on systemic and hepatosplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 44 publications
(115 reference statements)
0
27
0
Order By: Relevance
“…Norepinephrine and dopamine have a similar impact on hepatosplanchnic blood flow in septic patients but have differing effects on hepatic energy balance Vasoplegic patients were randomized to either drug in this crossover study to maintain a MAP greater than 80 mmHg [10 ]. Patients had similar rates of hepatosplanchnic blood flow in each group.…”
Section: Norepinephrinementioning
confidence: 99%
“…Norepinephrine and dopamine have a similar impact on hepatosplanchnic blood flow in septic patients but have differing effects on hepatic energy balance Vasoplegic patients were randomized to either drug in this crossover study to maintain a MAP greater than 80 mmHg [10 ]. Patients had similar rates of hepatosplanchnic blood flow in each group.…”
Section: Norepinephrinementioning
confidence: 99%
“…Published data in sepsis suggest that dopamine may impair hepatosplanchnic perfusion and metabolism (9,12,13). Tachycardia, another adverse effect of dopamine, together with vasoconstriction can lead to increased cardiac oxygen demand and decreased oxygen delivery and may trigger myocardial ischemia and arrhythmias.…”
Section: Dopaminementioning
confidence: 99%
“…In the selection of drugs for increasing the blood pressure about shock in recent years, norepinephrine has shown to be effective for improving blood fl ow of the viscera. [8,9] So we used norepinephrine to increase the blood pressure and found that in the hypertransfusion group, CO and HR were significantly increased after blood pressure increased, resulting in DO 2 in this group much higher than that in the control group, then improving tissue oxygen supply. Although VO 2 was increased simultaneously in the hypertransfusion group, ERO 2 was lower than that in the control group, indicating that hypertransfusion was effective to improve the oxygen metabolism.…”
Section: Discussionmentioning
confidence: 99%